2020
DOI: 10.1021/acs.jpca.9b11915
|View full text |Cite
|
Sign up to set email alerts
|

Toward Accurate Theoretical Vibrational Spectra: A Case Study for Maleimide

Abstract: We employ and combine a number of recent developments in vibrational structure methods to push their current size limitations toward molecules with tens of modes and showcase their availability for the maleimide molecule. In particular, we assess the use of different rectilinear vibrational coordinates, namely, normal coordinates, hybrid optimized and localized coordinates, and flexible adaptation of local coordinates of nuclei coordinates. These different coordinate parameterizations are employed in conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Moreover, it would be interesting to apply the PsCs in calculations of medium- to large-sized molecules in full dimensionality, either on their own or in comparison with different rectilinear sets of coordinates. A comparison to the performance of FALCON coordinates would, in this regard, be of special interest, as this set of rectilinear coordinates are known for a large degree of locality. , It has already been demonstrated that the Tana program is able to handle molecules as large as benzopyran and even larger molecules can be considered. The MidasCpp has been demonstrated to be able to handle molecules with up to hundredths of modes in both PES construction, using the ADGA, and in VCC calculations of the anharmonic vibrational wave function .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it would be interesting to apply the PsCs in calculations of medium- to large-sized molecules in full dimensionality, either on their own or in comparison with different rectilinear sets of coordinates. A comparison to the performance of FALCON coordinates would, in this regard, be of special interest, as this set of rectilinear coordinates are known for a large degree of locality. , It has already been demonstrated that the Tana program is able to handle molecules as large as benzopyran and even larger molecules can be considered. The MidasCpp has been demonstrated to be able to handle molecules with up to hundredths of modes in both PES construction, using the ADGA, and in VCC calculations of the anharmonic vibrational wave function .…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparison of different vibrational coordinates for maleimide in full vibrational space found that FALCON coordinates can support high accuracy of a few cm −1 . [40] It should be noted, however, that converging the results for the different coordinate systems to a common value turned out surprisingly difficult despite a rather high order in the truncations, that is, up to four-mode couplings in the potential energy surface and four-mode correlations in the VCC cluster operator (VCC [4]). Such full-space FALCON coordinates have further been combined with fragmentation schemes to allow the highly efficient generation of potential energy surfaces.…”
Section: Spanning the Vibrational Spacementioning
confidence: 99%
“…Its generation is not in the scope of the present perspective, but a few comments are appropriate: The challenges of generating the potential energy surface increase tremendously with system size. However, its generation can benefit from similar approaches as described above: This includes adaptively choosing the MCR of the typically applied n-mode expansion [46,16,40] , as well as similar multiscale [43,44,45] and fragmentation [41,6,45] ideas for the underlying electronic energy points. Another critical challenge is the treatment of rather flexible structures with a large manifold of local minima on the potential energy surface.…”
Section: The Potential Energy Surfacementioning
confidence: 99%
“…[ 21–24 ] The interested reader is referred to the excellent literature describing the actual algorithms, their capabilities and applicability. [ 21,25–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The interested reader is referred to the excellent literature describing the actual algorithms, their capabilities and applicability. [21,[25][26][27][28] We shall refer here solely to the commonly used VPT2 approaches (see for instance the review by Barone [29] ) on which major improvements have been recently proposed in order to account for the description of the elusive resonances through diagonalization of specific polyad matrices (groups of fundamentals, overtones, and/or combination matrices). [19,22,30] Very recently, machine learning techniques have been shown to provide excellent results in this respect.…”
mentioning
confidence: 99%